1997
DOI: 10.1017/s000156600000074x
|View full text |Cite
|
Sign up to set email alerts
|

The Twinning Rates and Epidemiological Characteristics of Births in Southeast Uttar Pradesh, India

Abstract: Birth statistics over a period of 5 years were analyzed to study epidemiological characteristics of twinning in Southeast Uttar Pradesh, India. The data revealed higher incidence of breech twins (11.84% of all cotwins) as compared to breech single births (2.18%). But the perinatal mortality and caesarean section rates were similar in both twin and singleton pregnancies. The cumulative twinning rate over the studied period was 11.70 per 1000 live births. The MZ and DZ twinning rates were estimated respectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
1
2
1
Order By: Relevance
“…There were a total of 18 reliable questions with which the physical similarity quotient (PSQ) was calculated. The prevalence rate of MZ and DZ twins in this study was 1:3, which is in accordance with previously published literature (Sharma, 1997). Carroll et al (2005) reported an MZ-to-DZ ratio of 1:2.…”
Section: Discussionsupporting
confidence: 93%
“…There were a total of 18 reliable questions with which the physical similarity quotient (PSQ) was calculated. The prevalence rate of MZ and DZ twins in this study was 1:3, which is in accordance with previously published literature (Sharma, 1997). Carroll et al (2005) reported an MZ-to-DZ ratio of 1:2.…”
Section: Discussionsupporting
confidence: 93%
“…The present study reported a higher incidence of twinning (34%) as compared with other studies from north and south India [7,8]. This is due to the fact that the study hospital was the only dedicated Covid-19 hospital providing maternity care for pregnant women with Covid-19 in Mumbai, and thus received all referral cases from Mumbai city and the nearby regions.…”
Section: Discussioncontrasting
confidence: 44%
“…as compared with other studies from north and south India. 7,8 This is due to the fact that the study hospital was the only dedicated COVID-19 hospital providing maternity care for pregnant women with COVID-19 in Mumbai, and thus received all referral cases from Mumbai city and the nearby regions. In addition, the majority of women with MGP in the present study conceived through assisted reproductive technology, resulting in a higher twinning rate.…”
Section: Discussionmentioning
confidence: 99%
“…No significant variation was reported in Brazil, 1984(Krieger et al 1996), in Greece, 1980-1985(Kataki and Kouvatsi 1988), or in Iran, 1975-1983(Farhud et al 1986). Meanwhile, positive seasonality of twinning was reported in Turkey (higher rates in May-August) (Duyar and Guntay-Ayaz 1993), in Bangladesh (both for DZ and MZ twins) (Razzaque et al 1990), and in India (Sharma 1997). In Denmark, a fifth-order polynomial curve with peaks in twin birth rates in May-June and December, along with troughs in February and September, was indicated for a series of data between 1977 and 1984 (Bonnelykke et al 1987).…”
Section: Discussionmentioning
confidence: 98%